Knowledge of Regulation of Photosynthesis in Outdoor Microalgae Cultures Is Essential for the Optimization of Biomass Productivity - Perin, Giorgio; Gambaro, Francesca; Morosinotto, Tomas (Frontiers in Plant Science, 2022)
Microalgae represent a sustainable source of biomass that can be exploited for pharmaceutical, nutraceutical, cosmetic applications, as well as for food, feed, chemicals and energy. To make microalgae applications economically competitive and maximize their positive environmental impact, it is however necessary to optimize productivity when cultivated at a large scale. Independently from the final product, this objective requires the optimization of biomass productivity and thus of microalgae ability to exploit light for CO2 fixation. Light is a highly variable environmental parameter, continuously changing depending on seasons, time of the day and weather conditions. In microalgae large scale cultures, cell self-shading causes inhomogeneity in light distribution and, because of mixing, cells move between different parts of the culture, experiencing abrupt changes in light exposure. Microalgae evolved multiple regulatory mechanisms to deal with dynamic light conditions that, however, are not adapted to respond to the complex mixture of natural and artificial fluctuations found in large-scale cultures, which can thus drive to oversaturation of the photosynthetic machinery, leading to consequent oxidative stress. In this work, the present knowledge on the regulation of photosynthesis and its implications for the maximization of microalgae biomass productivity are discussed. Fast mechanisms of regulations, such as Non-Photochemical-Quenching and cyclic electron flow, are seminal to respond to sudden fluctuations of light intensity. However, they are less effective especially in the 1-100 seconds time range, where light fluctuations were shown to have the strongest negative impact on biomass productivity. On the longer term, microalgae modulate the composition and activity of the photosynthetic apparatus to environmental conditions, an acclimation response activated also in cultures outdoors. While regulation of photosynthesis has been investigated mainly in controlled lab-scale conditions so far, these mechanisms are highly impactful also in cultures outdoors, suggesting that the integration of detailed knowledge from microalgae large-scale cultivation is essential to drive more effective efforts to optimize biomass productivity.